Maximizing Business Benefit in the Context of Globalization Role of Government, Employers, Global Actors and Female Employees - Karim, M.R. (University of Sri Jayewardenepura, Nugegoda., 2014)
Global market is open for all to maximize profit and accelerate business where a country necessitates knowing the details about opportunities, business strengths and fixing strategies in order to get the competitive advantages competing with other copious factors and potential multiple actors. Bangladesh is much exposed to the global market and encourages private sectors, especially readymade garments industry emerged in 1980s. According to Bangladesh Bureau of Statistics (2010) this sector has become the second largest export-oriented industries significantly contributing to the national economy. The high rate of unemployment in Bangladesh creates an abundance of cheap labor that attracts foreign buyers. Although globalization has brought some negative aspects, it also comes with myriad possibilities for socioeconomic benefits as benign effects. In order to maximize profit and business advancement, globally exposed businesses largely depend on fixing the strategies of business, meeting the employment standards, adhering to government rules and regulations, understanding and exploiting global market and meeting the demand of global actors. This paper is developed based on secondary data collected from journals, books, reports, World Bank publications, national and international daily newspapers, and annual publications of different ministries of Bangladesh. Literature suggests that three major parties i.e. the Bangladesh government, employers and foreign buyers try to gain maximum benefit from the global market. The Bangladesh government has enacted public policies for investment for both foreign and local to utilize huge unutilized workforce for economic development of the country. Employers take the advantage of government policies and cheap labor. Foreign buyers also demand special provisions from government and competitive price in the market. The ultimate issue is the working people in the central focus who build the triangular relation and contribute in this sector. However, they are ignored as they are poorly paid, forced to work in bad working conditions, and not provided proper facilities according to labor laws. The objectives of this paper are to examine the role of the above mentioned actors and contributing factors, how working people, women in particular are utilized and exploited, and to find out the effective bargaining mechanism for greater benefit.
Keywords: Business; Employee; Private Sector; Global Actors; Government